Upaya Mengurangi Konsumsi Minuman Beralkohol di Kalangan Muda Lewat Kegiatan GEBRAK (Generasi Bebas Dari Alkohol): Efforts to reduce alcohol consumption among young people through GEBRAK - Yoan, Margaretha Wulan Puspita; Marpaung, Yosi Marin (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Alcohol consumption among young people has become a common practice. Based on interviews, the majority of youth in Association X in Jakarta frequently consume alcoholic beverages. A community service activity titled